EFFECT OF COOPERATIVE LEARNING MODEL TYPE GROUP INVESTIGATION ASSISTED PHET AND TEAMWORK SKILL ON STUDENTS CONCEPTUAL KNOWLEDGE - Rikcy Almeda; Sahyar Sahyar (Universitas Negeri Medan, 2017)
This research aim is to know whether conceptual knowledge of students taught by Cooperative Learning Model type Group Investigation assisted PhET is better than conventional learning; to know whether conceptual knowledge of students in above average is better than the student in below average; to know whether there is an interaction between Cooperative Learning Model type Group Investigation assisted PhET and teamwork skill in improving conceptual knowledge of students. This research is quasi experimental research. The population in this research is all the students in class X Semester 2 Nurul Hakim Islamic Boarding School in Academic Year 2016/2017. The sample taken by cluster random sampling technique as much as 2 classes, where the experiment class taught by Cooperative Learning Model type Group Investigation assisted PhET and control class taught by conventional learning. Instrument used in this research consist of conceptual knowledge test and questionnaire of teamwork skill that has been validated and reliable. Data in this research analyzed by two ways ANAVA. The result of this research shows that conceptual knowledge of students taught by Cooperative Learning Model type Group Investigation assisted PhET with value 75,33 is better than conventional learning with value 69,00; conceptual knowledge of students in above average of teamwork skill with value 75,15 is better than the student in below average of teamwork skill with value 69,53; there is an interaction between Cooperative Learning Model type Group Investigation assisted PhET and teamwork skill in improving conceptual knowledge of students with value 0,037. This interaction shows the conceptual knowledge of students is dominan in Cooperative Learning Model type Group Investigation assisted PhET in group of students who have above average of teamwork skill.